In vitro ovicidal and larvicidal activities of some saponins and flavonoids against parasitic nematodes of goats. Issue 14 (21st May 2018) - Santos, Acidália Carine Vieira; Santos, Francianne Oliveira; Lima, Hélimar Gonçalves; Silva, Gisele Dias Da; Uzêda, Rosangela Soares; Dias, Êuder Reis; Branco, Alexsandro; Cardoso, Klauber Viana; David, Jorge Mauricio; Botura, Mariana Borges; Costa, Silvia Lima; Batatinha, Maria José Moreira
Abstract: This study assessed the anthelmintic activity of plant-derived compounds against gastrointestinal nematodes of goats using the egg hatch and larval motility assays. The compounds tested were saponins (digitonin and aescin) and their respective sapogenins (aglycones), hecogenin acetate and flavonoids (catechin, hesperidin, isocordoin and a mixture of isocordoin and cordoin). Additionally, cytotoxicity of active substances was analysed on Vero cell through 3-4, 5-dimethylthiazol-2-yl, 2, 5diphenyltetrazolium bromide (MTT) and propidium iodide (PI) tests. Significant reduction on the egg hatching ( P < 0.05) was seen only in the treatments with aescin (99%/EC50 = 0.67 mg mL −1 ) and digitonin (45%). The compounds that reduced the larval motility ( P < 0.05) were digitonin (EC50 = 0.03 mg mL −1 and EC90 = 0.49 mg mL −1 ) and the hecogenin acetate (75%). The other sapogenins showed low anthelmintic activity. All the flavonoids showed low ovicidal (4–12%) and larvicidal (10–19%) effects. The aescin and digitonin showed low toxicity in PI test (viable cells >90%). Nevertheless, higher cytotoxicity was observed in the MTT assay, with IC50 of 0.20 mg mL −1 (aescin) and 0.0074 mg mL −1 (digitonin). Aescin and digitonin have a pronounced in vitro anthelmintic effect and the glycone portion of these saponins plays an important role in this activity.